Isolated Pneumomediastinum Following Laparoscopic Cholecystectomy: An - Aydin, C; Akbulut, S; Gozeneli, O; Kahraman, A; Kayaalp, C (2014)
Pneumomediastinum is a clinical event characterized by the presence of air in the mediastinum. Often a result of physical trauma, this condition results from air escaping from the respiratory airway and moving into the mediastinal cavity. Although rare, it can also develop following abdominal laparoscopic surgical procedures. Diagnosis is commonly made by visualizing a radiolucent airline in the mediastinum and/or surrounding the heart following a chest X-ray radiography or a thoracic CT scan. This case study describes the diagnosis, treatment and follow-up of a 51 years old female patient who developed pneumomediastinum following a laparoscopic cholecystectomy. C1 [Aydin, Cemalettin; Akbulut, Sami; Gozeneli, Orhan; Kayaalp, Cuneyt] Inonu Univ Fac Med, Div Liver Transplantat, Dept Surg, TR-44280 Malatya, Turkey. [Kahraman, Aysegul] Inonu Univ Fac Med, Div Liver Transplantat, Dept Radiol, TR-44280 Malatya, Turkey.